The difference in severity and management between children and adult's cases of COVID-19 - Mohammad Husin; Gina Noor Djalilah; R A Kaniraras; Afrita Amalia Laitupa (Universitas Muhammadiyah Surabaya, 2021)
AbstractCOVID-19 (Coronavirus Disease 2019) has been started in Wuhan, China, and spread worldwide and resulting in many cases of death. COVID-19 attacks the respiratory tract acutely and infected both children and adults. The number of cases in children is less than in adults. By seeing from the clinical aspect, the COVID-19 case in children is milder. There are differences in immunology responses in children and adults where children have higher immunology response of COVID-19 than adults. Meanwhile, if the immunology response is slow in adults, it may cause them infected by COVID-19 with severe symptoms. There are some relations between immunization with immunology response to SARS-CoV-2 where children who already have BCG vaccination has lower infection rates of acute respiratory tract case. This study aims to know the difference between COVID-19 cases that infected adults and children seen in various aspects.Keywords : COVID-19,SARS-CoV-2, children, adult, severity, managementCorrespondence : mohammad_husin@yahoo.com